Endometritis secondary to infected abortion – Case report - Caldana , Nárima; Navarro , Méllanie; Correia , Victor Manoel da Silva (Seven Editora, 2023)
Early pregnancy loss takes many forms, with miscarriage being the loss that occurs in the first trimester of pregnancy. We can subdivide abortion into different forms, namely: spontaneous, retained, unavoidable, incomplete, recurrent, complete and septic abortion. Septic abortion is defined as any abortion that evolves to a more complicated condition due to the presence of endometritis, parametritis or infection of the upper genital tract and the treatment usually includes the use of antibiotic therapy, associated with evacuation of the retained conceptus. In this case report, the patient (female and 34 years old) presented bleeding at 14 weeks of gestation associated with vaginal discharge of contents similar to "flesh", foul odor and high fever. The diagnostic hypothesis was that she had an infected abortion, and she was requested for complementary tests, and she was referred for uterine emptying associated with antibiotic therapy. The patient progressed with improvement of clinical symptoms and was discharged from the service with the use of antibiotics. However, the patient returned 9 days later with abdominal pain in the lower abdomen with greenish discharge and ultrasound with signs suggestive of endometritis. The patient underwent magnetic resonance imaging that confirmed the hypothesis associated with a risk of sepsis, therefore, she underwent subtotal hysterectomy and bilateral salpingectomy. DOI:https://doi.org/10.56238/innovhealthknow-047